Firstly, you need to set the equation to 0. To do that, subtract both sides by 25: [tex] x^2+4x-21=0 [/tex] .
Next, we can complete the square. But first, what two terms have a product of -21x^2 and a sum of 4x? That would be 7x and -3x. Replace 4x in the equation with 7x - 3x: [tex] x^2 +7x-3x-21=0 [/tex]
Next, factor x^2 + 7x and -3x - 21 separately. Make sure that they both have the same quantity on the inside: [tex] x(x+7)-3(x+7)=0 [/tex]
Now you can rewrite the equation as [tex] (x-3)(x+7)=0 [/tex]
Now using zero product property, solve for x:
[tex] x-3=0\\ x=3\\ \\ x+7=0\\ x=-7 [/tex]
In short, your answer is A. x = 3 or x = -7.